Zhizn' na oshchup' . Life by Touch - Degtyar, Mikhail (TV Studio Reporter, 2008)
Verzio FF Submission The film is about blindness and blind people in Russia, about the choices they make and the alternatives they have. The filmmaker explores the notion of feeling and knowing the world not through images but by touch.